2021
DOI: 10.1136/bmjopen-2020-045642
|View full text |Cite
|
Sign up to set email alerts
|

Short-term and long-term survival in critical patients treated by helicopter emergency medical services in Finland: a registry study of 36 715 patients

Abstract: ObjectivesThis study aimed to describe the short-term and long-term mortality of patients treated by prehospital critical care teams in Finland.Design and settingWe performed a registry-based retrospective study that included all helicopter emergency medical service (HEMS) dispatches in Finland from 1 January 2012 to 8 September 2019. Mortality data were acquired from the national Population Register Centre to calculate the standardised mortality ratio (SMR).ParticipantsAll patients encountered by Finnish HEMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 25 publications
4
14
1
Order By: Relevance
“…Furthermore, a sufficient length of follow‐up is important. We have recently reported significant over‐mortality in patients treated by HEMS teams compared to the normal population, even 1‐to‐3 years after a critical incident 19 . In the current study, we observed a low frequency of severe disability in the survivors.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Furthermore, a sufficient length of follow‐up is important. We have recently reported significant over‐mortality in patients treated by HEMS teams compared to the normal population, even 1‐to‐3 years after a critical incident 19 . In the current study, we observed a low frequency of severe disability in the survivors.…”
Section: Discussionsupporting
confidence: 53%
“…We have recently reported significant over-mortality in patients treated by HEMS teams compared to the normal population, even 1-to-3 years after a critical incident. 19 In the current study, we observed a low frequency of severe disability in the survivors. The HRQoL in this study was higher than recently reported-for example, in patients with Parkinson's disease or head and neck cancer.…”
Section: Discussionsupporting
confidence: 51%
“…Previous studies have shown that the Finnish HEMS treat many intoxication cases with low mortality. 16 , 23 Because this might introduce bias and limit generalisability, we performed a sensitivity analysis excluding all intoxication patients. All the other factors remained identical to the original model in these sensitivity analyses.…”
Section: Methodsmentioning
confidence: 99%
“…The need for airway management during the pre-hospital phase was included in the analyses, as this has been shown to be strongly associated with subsequent mortality in this population [ 13 ]. In this study, tracheal intubation or the placement of a supraglottic airway device was considered advanced airway management.…”
Section: Methodsmentioning
confidence: 99%